Effects of enteral glutamine treatment on animal model of sepsis - Sulzbacher, Maicon Machado (2018)
The aim of study was to evaluate the effects of enteral glutamine treatment on clinical parameters in an animal model of sepsis. Were used 24 mice (B6129SF2/J) in two experiments: First 11 mice were divided into three groups to evaluate the animal model better to simulate the sepsis. Animals received saline (control) or faecal solution 10 or 20% (i.p), and were evaluated glycaemia and rectal temperature for 24h. Second 13 mice were divided into: Control, Sepsis, Glutamine and Sepsis+Glutamine. Glutamine was administered by gavage (1 g/kg) each 4h for 47h. Glycaemia, rectal temperature, leukocyte count and body weight was evaluated. Results: The administration of 20% faecal solution induced hypodynamic phase of sepsis with hypothermia, hypoglycaemia and low leukocyte count. The treatment with glutamine avoids the decrease in leukocyte. Conclusion: Since the immune response is essential in sepsis, the use of glutamine can be useful as adjuvant therapy in sepsis.